The problems encountered by English language students of Azzytuna University in translating English collocations into Arabic - Salah Alshaab Alzarouq Alazoumi (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
In life usage of language, people use collocations in their written as well as spoken language. Collocations are very important to produce correct and understandable language, thus collocations became the main concern of many researches. Therefore, this study aims to investigate the challenges encountered by English language students at Al-Qasi'a Collage when translating English collocations into Arabic. The experiment will involve eighteen sixth-semester students of English department during Spring 2025. These students, who are native Arabic speakers, are studying English as a foreign language. The research methodology includes a test comprising sixteen common English collocations, which the students are required to translate within one hour. The findings indicate a lack of proficiency among the participants in comprehending and translating English collocations into Arabic. The study also seeks to gain insights into the students' understanding of collocations and the difficulties they encounter when translating different types of collocations. The research will assess their awareness by examining their translations of English collocations into Arabic. The difficulties encountered in translating collocations were attributed to a variety of causes, including linguistic and cultural barriers, mistranslations of collocation definitions, and a tendency to rely on literal translations and word-for-word approaches. Notably, the findings suggested that the effectiveness of the university's translation education framework might play a role in the difficulties encountered in collocation translation, potentially highlighting deficiencies in the curriculum, teaching approaches, or student resources in terms of collocation translation abilities. The results highlight the main reasons for students' translation errors in collocations: a tendency to use literal translation and insufficient consideration of collocations specific to another culture and language. The key conclusion drawn is that collocations involve both linguistic and cultural aspects and go beyond mere word substitution in translation.